2006
DOI: 10.1017/s0001924000001627
|View full text |Cite
|
Sign up to set email alerts
|

Integration of friction stir welding into a multi-disciplinary aerospace design framework

Abstract: NOMENCLATURECER cost estimating relation DEE design and engineering engine FSW friction stir welding KBE knowledge based engineering t delay delay time before a manufacturing operation τ 0 time it takes to reach 63% of the steady state speed of a manufacturing process ν 0 steady state speed of a manufacturing process x variable on which manufacturing analysis are based, for instance length or area INTRODUCTIONTo remain competitive in a rapidly changing and customer driven industry manufacturers are implementin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In the aerospace domain, there is research [7] dealing with a system that automates design effort for blended wing bodies; [8] describing an application for the design of low pressure turbines. KBE systems are also developed for the design of manufacturing tools and processes [9,10]. By contrast, there are only few researches and applications in the railway manufacturing industry [11].…”
Section: Figurementioning
confidence: 99%
“…In the aerospace domain, there is research [7] dealing with a system that automates design effort for blended wing bodies; [8] describing an application for the design of low pressure turbines. KBE systems are also developed for the design of manufacturing tools and processes [9,10]. By contrast, there are only few researches and applications in the railway manufacturing industry [11].…”
Section: Figurementioning
confidence: 99%
“…In particular, MOKA provides no perspective on integrating KBE applications within multi-disciplinary design optimization (MDO), an area of considerable interest for both research and practice 2 . To address this, TU Delft researchers have devised the Design and Engineering Engine (DEE) approach [15][16][17][18] -see Figure 1. The DEE consists of three major elements, as indicated in the figure.…”
Section: Theoretical Contextmentioning
confidence: 99%
“…The modeling and analysis of parameters puts requirements on accuracy, as significant variation or uncertainty in design parameters may prevent model and analysis resolution. For instance, modeling and analysis of the Friction Stir Welding (FSW) joining process requires definition of weld dimensions (length, width, and area), which must fall within specific limits 15 for a successful weld given the constraints posed by the process and the available tooling, as well as the achievable tolerances. Reliability: how reliable is the captured knowledge?…”
Section: Step 2: (N)ormalizationmentioning
confidence: 99%
“…For the friction stir welding process it was shown that the estimated and real (sub)process times show significant correlation (van der Laan et al 2006). The calculation of the amount and type of materials used in the different subprocesses requires a different approach.…”
Section: Cost Analysis Functionsmentioning
confidence: 99%